Factores de riesgo y su relación con el desarrollo de las infecciones asociadas a la atención de salud en la área de UCI en el Hospital General Guasmo Sur periodo junio- octubre 2023. - Merizalde Santos, Jenipher Michelle (2023)
Objective: Determine the risk factors that influence the development of infections associated with health care in patients admitted to the ICU service of the Guasmo Sur general hospital. Methodological Design: the population with which we worked in this research work is made up of 25 people who are part of the health personnel who provide service to the ICU area of the Guasmo Sur General Hospital. An instrument was used that contained the corresponding variables for each objective to be developed related to general characteristics, admission criteria, procedures performed, identification of reported HAIs, data collection through observation, survey completion and tabulation were carried out by the researchers. which allowed the precise analysis and synthesis of research variables to obtain the necessary data. Results: From the health personnel who provide service at the Guasmo Sur General Hospital, 25 people who work in the ICU service were chosen. Among the results, it was found that there are risk factors that facilitate the appearance of these conditions, such as the state of patient health, cleaning and disinfection of medical equipment and hospital environment, some interventions and that there is no training for health personnel, since it occurs once a year, among the most frequent infections that occur in the hospital There is infection due to intubation, secondly, bacteremia, thirdly pneumonia associated with mechanical ventilation, urinary infection and finally surgical wound infection, all of which occur through interventions by health personnel, becoming a risk factor. For the appearance of this health problem, interventions include intubation, catheterization whether peripheral or central, nasogastric catheterization, mechanical ventilation and finally bladder catheterization. Conclusion: Different risk factors such as the patient's health status, cleaning and disinfection of medical instruments and hospital environments, the use of invasive procedures, among other interventions, are related to the development of infections associated with health care.